2014
DOI: 10.1097/aln.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Impairs γ-Aminobutyric Acid Receptor Type A–mediated Synaptic Transmission in the Murine Amygdala

Abstract: This study clearly demonstrates that TXA enhances neuronal excitation by antagonizing inhibitory GABAergic neurotransmission. The results provide evidence that this effect is mediated via postsynaptic mechanisms. Because GABAA receptor antagonists are known to promote epileptiform activity, this effect might explain the proconvulsant action of TXA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 37 publications
0
42
1
1
Order By: Relevance
“…TXA also increased the frequency of spontaneous epileptiform field potentials or “seizurelike events” (see Fig 1B) 47. Another study showed that application of TXA (1mM) to mouse amygdala slices caused widespread neuronal depolarization 49. Collectively, these studies show that TXA directly increases the excitability of neuronal networks.…”
Section: Molecular Mechanism Of Txa‐associated Seizuresmentioning
confidence: 77%
See 1 more Smart Citation
“…TXA also increased the frequency of spontaneous epileptiform field potentials or “seizurelike events” (see Fig 1B) 47. Another study showed that application of TXA (1mM) to mouse amygdala slices caused widespread neuronal depolarization 49. Collectively, these studies show that TXA directly increases the excitability of neuronal networks.…”
Section: Molecular Mechanism Of Txa‐associated Seizuresmentioning
confidence: 77%
“…Synaptic and tonic currents are mediated by different receptor subtypes that often exhibit different pharmacological properties 60. Surprisingly, the potency of TXA for synaptic currents (IC 50  = 0.8mM) and tonic inhibitory currents (IC 50  = 1mM) was similar 47, 49. Thus, although inhibition of GABA A receptors may contribute to TXA‐associated seizures, higher affinity target receptors are likely to exist in the CNS.…”
Section: Molecular Mechanism Of Txa‐associated Seizuresmentioning
confidence: 99%
“…TXA is perceived to be an antifibrinolytic agent, but is known to interact with multiple receptors [17]. TXA has recently been suggested to improve platelet function in patients on dual antiplatelet therapy [18], but the mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms are not fully elucidated, two studies have suggested possible mechanisms. Kratzer et al suggested that TXA enhances neuronal excitation by antagonizing inhibitory γ‐aminobutyric acid (GABA) neurotransmission. Lecker et al showed that TXA inhibits neural glycine receptors, whereas inhibition of the inhibiting neurotransmitter glycine is an established cause of seizures.…”
Section: Main Articlementioning
confidence: 99%